Germany 1945 : Views of War and Violence - Barnouw, Dagmar (Book collections on Project MUSE., 1996)
Stunning documentary photographs are the focus of this compelling study of postwar Germany and the battle over history, memory, and the German past. After half a century, Germany's coming to terms with Nazism remains a subject of debate. This investigation of the photographic record shows that such debates have overlooked the actual conditions in which postwar German memory was first forged. The Allied forces that entered Germany at the close of World War II were looking for remorse and open admissions of guilt from the Germans. Instead, they "saw" arrogance, servility, and a population thoroughly brainwashed by Nazism and in need of moral and political rehabilitation. For the Allies, the fundamental reality of Nazism was to be found in the death camps. Allied photography sought not only to document Nazism's violence but also to depict Germans finally seeing the truth of the regime in all its ghastly horror. Dagmar Barnouw argues that the German response could hardly have suited the victors' expectations. Demoralized, many uprooted from communities in which their families had lived for centuries, traumatized by the effects of wartime bombing, and weakened by sickness and near-starvation, Germans were concerned with survival, not with guilt over their Nazi past. Indeed, for many Germans, except for the last stages of the war, the memory of life under the Nazi regime was a largely positive one. In pointing this out, Barnouw does not offer an alternative truth or a revision of the scholarly record. Instead, she argues that postwar photography holds many possible, partial meanings that could be used to reassess our understanding of the recent German past. She uses Allied and German photographs to tease out these potential meanings, often reading images against their grain to suggest nuances and absences that the photographers themselves never intended or only partially understood